Internet addiction and depression among university students at school of health sciences, Universiti Sains Malaysia during the COVID-19 pandemic - Zaabah, Intan Lyana (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
Deteriorating mental health among university students during the COVID-19 pandemic is a serious worldwide public health concern. Internet addiction issue risen during COVID-19. This study aims to study internet addiction (IA) and depression among university students in School of Health Sciences, USM. This study is a cross-sectional study. We collected data from 122 students from January 2022 to March 2022 via convenience sampling. Internet addiction was measured using 26-items validated by Chen Internet Addiction (CIAS). Depression was measured using 10 items validated by the Center for Epidemiological Studies–Depression (CES-D) scale. Descriptive, Pearson Chi-square, Fisher's Exact test and Pearson's Correlation test were used in this study. There were 122 respondents who participated in this study and mostly 78.7% female students participated. The most of the respondents were Year Two students (37.7%). The residence of the respondents mostly from hostel or campus (54.1%). The time spent on internet per day mostly more than five hours (92.6%) per day. 44 students (36.1%) shown as internet addict. 75.4% were mildly depressed. There is a significant, moderate and positive correlation between internet addiction and depression (r =0.481, p <0.001). There is no significant association between sociodemographic characteristics and internet addiction (p>0.05). This study implies that lowering the time spent on internet per day is necessary to reduce the hazards to university students' mental health such as depression.